DETERMINING THE SAFETY OF POULTRY SUFFERING FROM EYMERIOZ - Щербакова, Н. С. (Scientific Progress & Innovations, 2013)
The estimation of safety of meat chickens suffering from eymerioz. The data to determine the toxicity of poultry rapid method using ciliates Colpoda steinii. Furthermore justified veterinary-sanitary evaluation of meat patient with eymerioz bird that is the meat derived from poultry patient with signs of exhaustion, is toxic and should be sent to the technical utilization. If meat obtained from patients poultry carcass but no signs of exhaustion, can produce the realization after inactivation by boiling thoroughly within three hours of outdoor boilers.